THE RELATIONSHIP BETWEEN GOVERNMENT MOTIVATION AND COMMUNICATION WITH PUBLIC WILL TO DO COVID-19 BOOSTER VACCINATION IN TANETE RIATTANG SUB-DISTRICT, BONE DISTRICT - Arranury, Zilfadhilah; Sahib, Nur Hildha; Basri, Syahrul; Surahmawati, Surahmawati (Homes Journal: Hospital Management Studies Journal, 2023)
Background: Covid-19 is an infectious disease caused by the latest variant of the coronavirus. This virus spreads quickly and widely so that it takes a lot of victims. As an effort to reduce the number of cases of Covid-19 is to vaccinate. But it's not enough just to vaccinate doses 1 and 2, now the government is again advising the public to do a booster vaccination for Covid-19. Aims: This study aims to determine the relationship between government motivation and communication with the community's willingness to carry out the Covid-19 booster vaccination in Tanete Riattang District, Bone Regency. Method: The type of research used is quantitative with a cross-sectional approach. The number of samples in this study were 395 respondents who were determined using a purposive sampling technique. Result: Based on the results of the bivariate test, it showed that there was a relationship between motivation (p = 0.012) and government communication (p = 0.013) with the public's willingness to carry out the Covid-19 booster vaccination. Recommendations for the government in Tanete Riattang District to make the Covid-19 booster vaccination an administrative requirement so that people want to do the Covid-19 booster vaccination